Characterization and structural basis of D-cysteine desulfhydrase from Pectobacterium atrosepticum. (9th January 2023) - Xu, Xuexia; Yang, Linsong; Zhang, Xianfang; Xing, Xiwen; Zhou, Jiahai
Abstract: d -cysteine desulfhydrase belongs to the family of lyases and participates in cysteine metabolism. Here we report the identification and crystal structures of D-cysteine desulfhydrase from Pectobacterium atrosepticum . The pyruvate-bound complex structure reveals a geminal diamine intermediate trapped in the active site and enables us to build the enzyme-substrate interaction model by molecule docking. Site-directed mutagenesis on R221 or Y264, one of the two critical residues in substrate binding pocket, results in mutants with enhanced enzyme activity toward D-cysteine carbon-sulfur lysis.